Revolutionizing Islamic Religious Education: Transforming Paradigms from Al-Azhar in Anticipation of the Future - maftuhah, maftuhah; Khozin, Khozin; Nurhakim, Moh. (Naturalistic: Jurnal Kajian dan Penelitian Pendidikan dan Pembelajaran, 2024)
Islamic religious education has undergone a substantial metamorphosis over time, reflecting the dynamics of societal development and the changing demands of the era. This article delineates the journey of the Islamic religious education revolution through paradigm shifts that occurred at Al-Azhar, a prominent institution of higher education in the Islamic world. Through a deep historical analysis, this article explores the significant steps taken by figures such as Muhammad Ali Pasha, Muhammad Abduh, and Muhammad Rashid Rida in bringing about changes to the Al-Azhar curriculum. The process of renewal not only encompasses the integration of modern elements from the West but also involves responding to the challenges of the times. This article details the role of Al-Azhar in creating a new foundation that enables Islamic religious education to face the future more dynamically and relevantly